Sie sind auf Seite 1von 14

a b a < b R

[a, b] = {x R | a x b}

(a, b) = {x R | a < x < b}

[a, b) = {x R | a x < b}

(a, b] = {x R | a < x b}

(−∞, b) = {x R | x < b}

(−∞, b] = {x R | x b}

(a, ) = {x R | a < x}

[a, ) = {x R | a x}

(−∞, ) = R

a R ε R ε > 0

K ε (a) := (a ε, a + ε) ε a

K ε () := ( 1 ε , ) ε

K ε (−∞) := (−∞, 1 ε ) ε −∞

x R y K ε (x) |x y| < ε

A A R A A A

f D f R f f x f (x) y = f (x) y x x y

f

{(x; f (x)) | x D f }

f

f : A B y B x A x x y = f (x)

f : A B y B x A y = f (x) y B x A

f : A B f y B x A

f g c

cf D f f c f

f + g f g f · g f g f g D f+g = D fg =

D f·g

= D f D g

f

g

f g

= (D f

=

D f D g g

D g ) \ {x | g(x) = 0}

0

D f

g

g f f g x f (g(x)) f g

x D g g(x) D f

f f

 

˜

f

f

x f x

˜

f (x) f ( f (x)) = x

˜

f x D f x D f f (x) = f (x) f (x) = f (x)

f p > 0 x D f x + p D f x p D f f (x + p) = f (x p) = f (x)

f I I D f k R K R f (x) k f (x) K x I

I D f f

x 1 , x 2 I

x 1 < x 2 f (x 1 ) f(x 2 )

f I

x 1 , x 2 I

x 1 < x 2 f (x 1 ) < f(x 2 )

f I

x 1 , x 2 I

x 1 < x 2 f (x 1 ) f(x 2 )

f I

x 1 , x 2 I

x 1 < x 2 f (x 1 ) > f(x 2 )

f I

f (x) = ax + b

a b y

f (x) = ax 2 + bx + c

( D = b 2 4ac

b

2a ;

D

4a )

f (x) = a n x n +

a 1 x + a 0 a n = 0

n a k x k

f (x) = x n n N \ {0} x n x n x n

f (x) = n

a a R a > 0 f (x) = exp a (x) = a x

= 1

x

n x n N \ {0; 1}

a a R a > 0 a

f (x) = log a (x)

x

x

x

x |x|

sin x x cos x x

x

sin(x) = sin x

sin(x + k · 2π) = sin x k Z 2π

k Z

1 1

D = R R = [1, 1]

[π

2 + k · 2π, π

2

+ k · 2π] k Z

+ k · 2π, 3π + k · 2π]

[ π k Z

2

2

π , π arcsin

2

2

sin(arcsin x) = x

arcsin(sin x) = x

x [1, 1],

x π , π .

2

2

[0, π] arccos

cos(arccos x) = x

x [1, 1],

arccos(cos x) = x

x

[0, π] .

π , π

2

2

( x) = x

( x) = x

x (−∞, ),

x π , π .

2

2

(0, π)

( x) = x

x (−∞, ),

( x) = x

x

(0, π) .

α −∞ f α

f α β

ε > 0 δ > 0 f (x) K ε (β) x K δ (α) x

= α

lim

xα f (x) = β f (x) β x α

α R f α f

α β ε > 0 δ > 0

f(x) K ε (β) x K δ (α) x

= α

xα f (x) = β f (x) β x α

lim

α R f α f α β ε > 0 δ > 0

f (x) K ε (β) x K δ+ (α) x

= α

xα+ f (x) = β f (x) β x α+

lim

f α β f α β f α f α

f g α β f β g

c · f α c R lim

xα c · f(x) = c · β g

f ± g α lim

xα f(x) ± g(x) = β f ± β g

f · g α lim

xα f(x) · g(x) = β f · β g

f α β g = 0 lim

g

xα

f(x)

g(x)

= β β f g

x→∞ c x =

lim

,

1,

0,

c > 1, c = 1,

0 < c < 1.

n > 0

x x n =

lim

c R

x→−∞ x n =

lim

,

−∞,

lim

x0

sin x

x

= 1.

x→∞ lim 1 +

c

x

x = e c ,

n n

e e = 2.71828182

lim

x0

log a (1 + x)

1

=

x

ln a .

f α D f f α

xα f(x) = f(α).

lim

f α D f f α α

xα f(x) = f(α).

lim

f α D f f α α

xα+ f(x) = f(α).

lim

f g α f ± g

f · g g(α)

g α f g(α)

f g α

= 0 f

g

α

f x f x

lim

h0

f(x + h) f(x)

h

f x f (x) f x

f(x+h)f(x)

h

f

f : x

f (x),

x D f f f (x) f

f x f x

f x

f x x + h h 0

f(x + h) = f(x + h) f(x)

h

f (x) ·

0

f x

h

0

+ f (x) · h +f(x) f(x).

0

f g I

c · f c R I (c · f ) = c · f

f ± g I (f ± g) = f ± g

f I g(x)

f ± g I

g

(f · g) = f · g + f · g

= 0 x I

f

g

= f ·gf·g

g 2

g I f g(x)

x I f g I

(f g) = (f g) · g .

f

˜

I f

˜

x I f f

˜

˜

f ( f (x))

I

= 0 f

˜ 1

f =

˜

f f

g =

˜

f

 

˜

˜

˜

 

1

= (f( f (x))) = f ( f (x)) · f (x),

˜

(f ( f (x))) = (x) = 1

f x 0 (x 0 ; f(x 0 )) f (x 0 ) f (x 0 ; f(x 0 ))

y f(x 0 ) = f (x 0 ) · (x x 0 ).

f I

f (x)

= 0 x I

E f (x) = x · f (x)

f(x)

f I f I

f g α α

xα g(x) = 0( − ∞)

xα f(x) =

g (x)

= 0 lim

lim

lim

xα

lim

xα

f

(x)

g

(x)

f(x)

g(x)

= β

= β.

f I f I f I

f x 0 K ε (x 0 ) D f x 0 f (x 0 ) f(x) f(x 0 ) f (x) x K ε (x 0 )

f x 0 I D f f (x 0 ) f(x) f(x 0 ) f (x) x I

f x 0 f x 0 f (x 0 ) = 0.

x f (x) = 0 f x 0 x 0 x f (x) < 0 x < x 0 f (x) > 0 x > x 0

x 0 f f x 0 f x 0

x 0 f f (x 0 ) = f (x 0 ) =

··· = f (m1) (x 0 ) = 0 f (m) (x 0 )

= 0 f

m x 0

m x 0 f (m) (x 0 ) > 0 x 0 f (m) (x 0 ) < 0

[a, b] [a, b]

I

I I I

x 0 f x 0 (x 0 ; f(x 0 )) (x 0 ; f(x 0 ))

±∞

f x 0 n n

T n (x) = f(x 0 )+f (x 0 )·(xx 0 )+ f (x 0 ) ·(xx 0 ) 2 +···+ f (n) (x 0 ) ·(xx 0 ) n

2!

n!

n f x 0

f x 0 n

T n (x 0 ) = f(x 0 ), T n (x 0 ) = f (x 0 ), T (x 0 ) = f (x 0 ),

n

(n)

, T

n

(x 0 ) = f (n) (x 0 ).

f x 0 n + 1 x 1 x x 0

f(x) T n (x) = f (n+1) (x 1 ) (x x 0 ) n+1

(n + 1)!

(a n ) K a R K f R a n K a a n K f n N (a n )

K a R K f R (a n )

(a n )

a n a n+1 n N

a n < a n+1 n N

a n a n+1 n N

a n > a n+1 n N

β −∞ (a n ) β ε > 0 δ > 0 a n K ε (β) n K δ ()

f (a n ) a n = f (n) β f β (a n )

T P n

T n n

100

r

= 1 +

P

T n = T +

100 P Tn = T 1 +

P 100 Tn

T 0 = T

T n = T n1 1 + T n = T · r n

T n = T · e

T n = A·r· r n 1 A

P

100 n = 1, 2,

Pn

100

= T · e n(r1)

r1

B · r n = A · r n 1 B A n

r1

f K a R K f R f (x, y) K a f (x, y) K f (x, y) D f

(x, y) R 2 ε R ε > 0 ε (x, y) K ε (x, y) (x, y) ε

K ε (x, y) = {(a, b) R 2 | (a x) 2 + (b y) 2 < ε}

f (x 0 , y 0 ) D f

f (x 0 , y 0 ) f (x, y) (x, y) K ε (x 0 , y 0 )

K ε (x 0 , y 0 ) D f (x 0 , y 0 ) f (x 0 , y 0 ) f (x, y)

f H D f R 2 f H (x 0 , y 0 ) H f (x 0 , y 0 ) f (x, y) f (x 0 , y 0 ) f (x, y) (x, y) H

β −∞ f (x 0 , y 0 ) (x 0 , y 0 ) f (x 0 , y 0 ) β ε > 0

δ > 0 f (x, y) K ε (β) (x, y) K δ (x 0 , y 0 )

β

(x, y)

= (x 0 , y 0 )

(x,y)(x 0 ,y 0 ) f (x, y) =

lim

f (x, y) β (x, y) (x 0 , y 0 )

f (x 0 , y 0 ) R 2 (x 0 , y 0 ) D f f (x 0 , y 0 )

(x,y)(x 0 ,y 0 ) f (x, y) = f (x 0 , y 0 ) .

lim

H R 2 H

f (x 0 , y 0 ) R 2

f x (x) = f (x, y 0 ) f y (y) = f(x 0 , y) f x y

(x 0 , y 0 )

f f x y x 0 y 0 f (x 0 , y 0 ) x y f x (x 0 ) f y (y 0 ) f x y

(x 0 , y 0 ) f x (x 0 , y 0 ) f (x 0 , y 0 )

f y (x 0 , y 0 ) f (x 0 , y 0 )

∂x

∂y

f f f y (x, y) f x y (x, y) f x (x, y) f y (x, y) f x y

x

f (x 0 , y 0 ) [f x (x 0 , y 0 ), f y (x 0 , y 0 )] f (x 0 , y 0 ) ( f )(x 0 , y 0 ) (x, y) f (x, y) f f

(x 0 , y 0 ) (x 0 , y 0 )

(x 0 , y 0 ) f f (x 0 , y 0 )

D(x, y) = f xx (x, y) · f yy (x, y) f xy (x, y) · f yx (x, y).

D(x 0 , y 0 ) > 0 (x 0 , y 0 ) f f xx (x 0 , y 0 ) > 0 (x 0 , y 0 ) f xx (x 0 , y 0 ) < 0 (x 0 , y 0 )

D(x 0 , y 0 ) < 0 f (x 0 , y 0 )

(x 1 , y 1 ),

y = mx + b

, (x n , y n )

σ(m, b) =

n

i=1

(mx i + b y i ) 2 min!

(m 0 , b 0 ) σ

m 0 = n

n

i=1 (x i · y i ) n · x¯ · y¯

i=1 (x i ) 2 n · x) 2

, b 0 = y¯ m 0 · x.¯